2022
DOI: 10.1097/pas.0000000000001920
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combined Tumor Budding-Poorly Differentiated Clusters Grading System Predicts Recurrence and Survival in Stage I-III Colorectal Cancer

Abstract: Tumor budding (TB) and poorly differentiated clusters (PDCs) are powerful prognostic factors in colorectal cancer (CRC). Despite their morphologic and biological overlap, TB and PDC are assessed separately and are distinguished by an arbitrary cutoff for cell cluster size. This cutoff can be challenging to apply in practice and its biological significance remains unclear. We developed a novel scoring system that incorporates TB and PDC into a single parameter ("Combined Score"; CS), eliminating the need for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This study adds to the growing body of evidence validating high-grade tumor budding (ITBCC Bd3) as an independent prognostic factor in surgically resected CRC 6–8,13,23–31 . In a large cohort of patients undergoing resection of stage I-III CRC with curative intent, high-grade TB (Bd3) was strongly associated with other adverse histologic features, cancer-related mortality and recurrence.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This study adds to the growing body of evidence validating high-grade tumor budding (ITBCC Bd3) as an independent prognostic factor in surgically resected CRC 6–8,13,23–31 . In a large cohort of patients undergoing resection of stage I-III CRC with curative intent, high-grade TB (Bd3) was strongly associated with other adverse histologic features, cancer-related mortality and recurrence.…”
Section: Discussionmentioning
confidence: 83%
“…This study adds to the growing body of evidence validating high-grade tumor budding (ITBCC Bd3) as an independent prognostic factor in surgically resected CRC. [6][7][8]13,[23][24][25][26][27][28][29][30][31] In a large cohort of patients undergoing resection of stage I-III CRC with curative intent, highgrade TB (Bd3) was strongly associated with other adverse histologic features, cancer-related mortality and recurrence. The prognostic significance of TB was independent of other adverse histologic factors in multivariable Cox proportional hazards analyses and was also present in resections performed after neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TB is an independent poor prognostic factor in colorectal cancer, and studies and meta-analyses have further validated that high-grade TB is significantly associated with lymph node metastasis in colorectal cancer ( P < 0.05) [ 15 , 30 ]. In addition, it was found that TB was significantly associated with poorer 5-year DFS, OS, and CSS in colorectal cancer ( P < 0.001), and TB showed the same correlation with 5-year DFS, OS, and CSS in the neoadjuvant subgroup [ 16 , 31 ]. However, the findings showed significant differences in the 5-year OS between rectal and colon cancers ( P ≤ 0.001) [ 32 , 33 ], and distinct differences in pathological manifestations, tumor immune microenvironments, and gene mutation profiles were found between tumor sites [ 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%